Atividade cicatrizante da própolis vermelha em feridas cirúrgica de gatas submetidas à ovariossalpingohisterectomia - Medeiros, Gerard Vicente Dantes de (Universidade Federal Rural do Semi-Árido, 2020)
The objective of this study was to evaluate the effect of the hydroethanolic extract of red propolis, produced by Apis mellifera in the semiarid region of Brazil, on the healing of surgical wounds in cats submitted to ovarisalpingohisterectomy. We also evaluate the chemical composition, cytotoxic effects and antioxidant activity of red propolis. The total phenol content was determined by the Folin Ciocalteu method and flavonoid by the spectrophotometry method. The chemical composition of the stratum was performed by the HPLC-DAD-ESI-MS/MS method. Antioxidant activity was evaluated by the DPPH method (2.2-diphenyl-1-picrilidrazyl) and cytotoxicity was evaluated by the MTT colorimetric method using L929 fibroblasts and HACAT keratinocytes exposed to different concentrations of red propolis extract (500, 250, 125, 62.5, 31.2 and 15.6 µg/mL) for 72 hours. The healing effect of the extract was evaluated in 60 domestic cats (Felis catus) distributed in three groups: Group I (test group) composed of 20 cats submitted to ovarisalpingofisterectomia treated with topical application of 0.2 ml of 50 mg / ml (EEPV); Group II (reference group) with 20 cats that also received topical application of 0.2 ml of commercial solution based on rifamicin (Rifocina®), and Group III (control group), also composed of 20 animals treated with topical application of 0.2 ml of 0.9% NaCl physiologic solution. The surgical wounds were evaluated for clinical, macroscopic and histological aspects on the 3rd, 7th, 14th and 21st post operative days. The ethanolic extract of red propolis showed 26 flavonoids, high values of total phenols and high antioxidant activity. Propolis extract had no cytotoxic effect on any of the cell lines tested. High percentages of cell viability were observed, ranging from 80.0% to 94.4% for L929 fibroblasts and 78.0% to 91.5% for Hacat ceratocytes. red propolis had a positive influence on the healing of wounds in cats submitted to ovarisalpingohisterectomy, because it promoted less intense inflammatory response, rapid closure of the wound, early deposition of collagen and reepithelization. Therefore, it was concluded that the ethanolic extract of red propolis did not exert cytotoxic effect in vitro, presented high levels of total phenols, different types of flavanoids, high antioxidant activity and promoted the acceleration of healing of surgical wounds.
Keywords: Apis mellifera; Flavonóides; Antioxidante; Cicatrização de feridas; CIENCIAS AGRARIAS::MEDICINA VETERINARIA